2019
DOI: 10.1155/2019/4250613
|View full text |Cite
|
Sign up to set email alerts
|

A Six-Gene Signature Predicts Survival of Adenocarcinoma Type of Non-Small-Cell Lung Cancer Patients: A Comprehensive Study Based on Integrated Analysis and Weighted Gene Coexpression Network

Abstract: Background and Goals. To identify a multigene signature model for prognosis of non-small-cell lung cancer (NSCLC) patients, we first found 2146 consensus differentially expressed genes (DEGs) in NSCLC overlapped in Gene Expression Omnibus (GEO) and TCGA lung adenocarcinoma (LUAD) datasets using integrated analysis. We constructed a weighted gene coexpression network (WGCN) using the consensus DEGs and identified the module significantly associated with pathological M stage and consisted of 61 genes. After univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 52 publications
(69 reference statements)
1
32
0
Order By: Relevance
“…6C-6E. We also compared our results with the two published gene signature studies (Xie & Xie, 2019;Zhao, Li & Tian, 2018) and found that the C-index results were better than their signatures (Table 2). Taken together, these results indicated a better predictive performance about our prognostic signature.…”
Section: Validation Of the Twenty-three Metabolic Gene Signaturesmentioning
confidence: 77%
See 1 more Smart Citation
“…6C-6E. We also compared our results with the two published gene signature studies (Xie & Xie, 2019;Zhao, Li & Tian, 2018) and found that the C-index results were better than their signatures (Table 2). Taken together, these results indicated a better predictive performance about our prognostic signature.…”
Section: Validation Of the Twenty-three Metabolic Gene Signaturesmentioning
confidence: 77%
“…Bioinformatics has contributed to determining the prognosis and treatment of LC (Parikh, 2019). There have been numerous studies on gene prognosis models that could contribute to the selection of LC treatment methods and the prediction of survival after LC surgery; for example, a prognostic signature containing six genes (RRAGB, RSPH9, RPS6KL1, RXFP1, RRM2, and RTL) to evaluate the prognosis of NSCLC patients (Xie & Xie, 2019). In another article on prognostic characteristics of LUAD, a prognostic model based on 20 genes was developed to predict patient overall survival (OS) (Zhao, Li & Tian, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The high-throughput sequencing technology has made it possible a comprehensive interrogation of whole transcriptome and genome of tumor tissues at an increasingly reasonable cost [4,5]. Previous studies focused on finding prognostic signatures based on gene expressio n [6][7][8][9] or mutation [10][11][12] for LUAD patients. For example, Li et al [7] reported gene expression-based models with an average C-index of 0.604 on testing datasets from TCGA-LUAD in predicting overall survival (OS).…”
Section: Introductionmentioning
confidence: 99%
“…The high-throughput sequencing technology has made it possible a comprehensive interrogation of whole transcriptome and genome of tumor tissues at an increasingly reasonable cost [4,5]. Previous studies focused on finding prognostic signatures based on gene expression [6][7][8][9] or mutation [10][11][12] for LUAD patients. For example, Li et al [7] reported gene expression-based models with an average C-index of 0.604 on testing datasets from TCGA-LUAD in predicting overall survival (OS).…”
Section: Introductionmentioning
confidence: 99%